Emotion Regulation in Rescue Workers: Differential Relationship With Perceived Work-Related Stress and Stress-Related Symptoms - Gärtner, Anne; Behnke, Alexander; Conrad, Daniela; Kolassa, Iris-Tatjana; Rojas, Roberto (Frontiers in Psychology, 2019)
Rescue workers are exposed to enduring emotional distress, as they are confronted with (potentially) traumatic mission events and chronic work-related stress exposure. Thus, regulating negative emotions seems to be crucial to withstand the work-related strain. This cross-sectional study investigated the influence of six emotion regulation strategies (i.e., rumination, suppression, avoidance, reappraisal, acceptance, and problem solving) on perceived work-related stress and stress-related depressive, posttraumatic, and somatic symptoms in a representative sample of 102 German rescue workers. Multiple regression analyses identified rumination and suppression to be associated with more work-related stress and stress-related symptoms. Acceptance was linked to fewer symptoms and, rather unexpectedly, avoidance was linked to less work-related stress. No effects were observed for reappraisal and problem solving. Our findings confirm the dysfunctional role of rumination and suppression for the mental and physical health of high-risk populations and advance the debate on the context-specific efficacy of emotion regulation strategies.